Impact of Kids Yoga on Preschoolers’ Gross Motor Skills - Ifyan, Rhenda Ainkarisma; Widiatrilupi, Raden Maria Veronika; Sulistiyah, Sulistiyah (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Gross motor development is a crucial aspect of early childhood growth and is significantly influenced by appropriate stimulation. Kids Yoga serves as an enjoyable form of physical stimulation by incorporating body movement, balance, coordination, and self-awareness. This study aimed to determine the effect of Kids Yoga on gross motor development in preschool children aged 4–6 years. A quantitative approach was employed using a pre-experimental one-group pretest-posttest design. The sample consisted of 16 children selected through purposive sampling at Dharma Wanita Persatuan 2 Kindergarten, Sumbersuko Village, Dampit District, Malang Regency. Inclusion criteria included: being 4–6 years old, enrolled as an active student, physically healthy, having motor impairments, and obtaining parental consent. The intervention was the Kids Yoga program, conducted over a period of four weeks, with sessions held twice a week, resulting in a total of eight sessions. Each session lasted 30–45 minutes and included three phases: warm-up and breathing, core yoga poses focused on balance and coordination, and cool-down or relaxation exercises. The program was delivered by certified Kids Yoga instructors, supported by the researcher. The instrument used for measuring gross motor development was the Test of Gross Motor Development-2 (TGMD-2). Data were analyzed using the non-parametric Wilcoxon Signed-Rank Test to compare pretest and posttest scores. Before the intervention, 4 children (25%) were in the “Poor” category and 12 (75%) in the “Fair” category. After the intervention, no children remained in the “Poor” category 9 children (56.25%) were categorized as “Fair” and 7 (43.75%) improved to the “Good” category. The Wilcoxon test showed a statistically significant difference with a p-value < 0.001. In conclusion, Kids Yoga has been proven effective in enhancing gross motor development and can serve as a beneficial and enjoyable alternative educational activity within early childhood education settings.